CONTROL AND ACCOUNTING INFORMATION SYSTEM USING COSO ERM IN PT. EMII - Syahputra, Faiz; Suardi, Imelda (Academic Research Centre Services, 2017)
The use of accounting information system effects the implementation of internal control. COSO ERM method is now the most widely accepted internal control framework in the world and used as the basis for this research. The case study was conducted in a medical equipment distributor that has implemented accounting information system for their financial reporting. The focus is on its process, threats, and controls using interview and questionnaire to the employess. This research proposed new procedures for both revenue and expenditure cycles and suggested activites for better internal control. The result showed that the company has implemented good internal control in almost all COSO ERM measurement, except for information and communication aspect.